A Preliminary Investigation of User Perception and Behavioral Intention for Different Review Types: Customers and Designers Perspective - Atika Qazi; Ram Gopal Raj; Muhammad Tahir; Mahwish Waheed; Saif Ur Rehman Khan; Ajith Abraham (The Scientific World Journal)
Existing opinion mining studies have focused on and explored only two types of reviews, that is, regular and comparative. There is a visible gap in determining the useful review types from customers and designers perspective. Based on Technology Acceptance Model (TAM) and statistical measures we examine users’ perception about different review types and its effects in terms of behavioral intention towards using online review system. By using sample of users (N=400) and designers (N=106), current research work studies three review types, A (regular), B (comparative), and C (suggestive), which are related to perceived usefulness, perceived ease of use, and behavioral intention. The study reveals that positive perception of the use of suggestive reviews improves users’ decision making in business intelligence. The results also depict that type C (suggestive reviews) could be considered a new useful review type in addition to other types, A and B.